Comprehensive review of SolidWorks and ANSYS for hydraulic machinery design and analysis - Krupa, Yevhenii; Demchuk, Roman (Impress, 2024)
An in-depth analysis of current computer-aided design (CAD) and systems engineering analysis (CAE) software is presented, focusing on SolidWorks and ANSYS. Particular attention is paid to their use in the design and analysis of hydraulic machines, where these tools play an essential role in the development of turbines, pumps, and other components. SolidWorks stands out as the leading tool for creating 3D models of hydraulic assemblies, allowing engineers to optimize designs and reduce hydraulic losses early in the design process. In addition, SolidWorks offers a user-friendly interface and powerful modeling capabilities, allowing you to perform fundamental analyses in a hydraulic simulation environment. A review of the widely used ANSYS program, recognized as a tool for performing complex engineering analyses covering a wide range of physical phenomena, including thermal, mechanical, electromagnetic, and hydrodynamic processes, is performed. The multiphysics capabilities of ANSYS allow engineers to model complex interactions of physical phenomena in a single simulation environment, which is especially important for tasks such as designing power plants or hydro turbines. A comprehensive review of simulation features, including Finite Element Analysis (FEA) and flow modeling, is performed to provide early detection of design problems. The application of ANSYS is proposed for the in-depth analysis of hydrodynamic phenomena occurring in turbines during their operation, which allows the optimization of the geometry of the blades and reduces the risk of cavitation. Furthermore, it is emphasized that integrating both software packages creates a powerful toolkit for engineers, allowing them to combine design and analysis in a single workflow. It is concluded that effective use of SolidWorks and ANSYS can significantly improve the quality of hydraulic machine development, reducing design time and increasing reliability. The article also provides practical examples of the use of these programs in real projects, demonstrating their effectiveness and impact on engineering solutions in the field of mechanical engineering.

Представлено глибокий аналіз сучасного програмного забезпечення для систем автоматизованого проєктування (CAD) та систем інженерного аналізу (CAE), з акцентом на SolidWorks та ANSYS. Особливу увагу приділено їх використанню в проєктуванні та аналізі гідравлічних машин, де ці інструменти відіграють важливу роль у розробці турбін, насосів та інших компонентів. SolidWorks виділяється як провідний інструмент для створення 3D-моделей гідравлічних агрегатів, що дозволяє інженерам оптимізувати конструкції та зменшувати гідравлічні втрати на ранніх етапах проєктування. Крім того, SolidWorks пропонує зручний інтерфейс і потужні можливості симуляції, дозволяючи виконувати базові аналізи безпосередньо в середовищі моделювання гідравлічних систем. Виконано огляд широко використовуваної програми ANSYS, що визнаний як інструмент для виконання складних інженерних аналізів, які охоплюють широкий спектр фізичних явищ, включаючи теплові, механічні, електромагнітні та гідродинамічні процеси. Мультифізичні можливості ANSYS дозволяють інженерам моделювати складні взаємодії фізичних явищ в єдиному середовищі симуляції, що є особливо важливим для таких завдань, як проєктування енергетичних установок або гідротурбін. Виконано всебічний огляд функцій симуляції, які включають аналіз кінцевих елементів (FEA) та моделювання потоків, що забезпечує раннє виявлення потенційних проблем у конструкції. Запропоновано застосування ANSYS для глибокого аналізу гідродинамічних явищ, що відбуваються в турбінах під час їх експлуатації, дозволяючи оптимізувати геометрію лопатей та зменшувати ризик кавітації. Додатково, підкреслено, що інтеграція обох програмних комплексів створює потужний інструментарій для інженерів, дозволяючи їм поєднувати проєктування та аналіз у єдиному робочому процесі. Зроблено висновок про те, що ефективне використання SolidWorks та ANSYS може значно покращити якість розробки гідравлічних машин, зменшивши час на проєктування та підвищивши їх надійність. У статті також представлено практичні приклади використання цих програм у реальних проєктах, що демонструють їх ефективність та вплив на інженерні рішення в галузі машинобудування.
Комплексний огляд SolidWorks та ANSYS для проєктування та аналізу гідравлічних машин
Keywords: SolidWorks; ANSYS; hydraulic machines; design; computational fluid dynamics; numerical research; SolidWorks; ANSYS; гідравлічні машини; проєктування; обчислювальна гідродинаміка; чисельне дослідження